Prenatal Visits as Determinants of Maternal Hemoglobin Level and Neonatal Birth Weight in Tertiary Care Hospital - Akhter, Aliya Nasim; Farhan Saeed; Erum Saboohi; Farhat Ali; Naima Shah; Neelofar Ghaffar (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To determine the association between the number of prenatal visits, maternal hemoglobin level, and birth weight of newborns. METHODOLOGY: This cross-sectional study was conducted in the Department of Obstetrics & Gyneacology, Darul Sehat Hospital, Karachi, from July 2022 to January 2023. Females with any parity and full-term gestational age, regardless of mode of delivery, were included, while patients with preterm deliveries, miscarriages, and referred cases were excluded. The convenience non-probability technique is a method of sampling. A questionnaire containing demographic information, the number of antenatal visits, and the timing of the first visit to the hospital, as well as Hb level at the time of birth and fetal outcome, was introduced. The Chi-square test was used to assess the association between variables. SPSS 21 was used for data calculation. RESULTS: 155 women were interviewed. The mean age of the respondents was 29±6.2 years, the mean parity was 2.2±1.07, and the mean number of visits was 6.3±3.2. 34% had eight or more visits. The mean gestational age at booking is 16.7±9.4 weeks, and the mean Hb level of the population is 10.1g/dl±1.2. 67% of the population is found to be anemic. A p-value of (0.04) indicates a relationship between the mother’s hemoglobin level and prenatal visits. 52.3% of newborns were born with low birth weights. CONCLUSION: Prenatal attendance is significantly associated with maternal hemoglobin level and neonatal birth weight. The number and quality of prenatal visits must be ensured at the national level to improve maternal and neonatal health.